(untitled) (One Health & Risk Management, 2021)
Introduction. Multimorbidity is a global health challenge, and it’s commonly defined as the coexistence of 2 or more chronic diseases in the same individual. Roughly 50 million people in Europe suffer from multimorbidity across all ages and backgrounds. The management of multimorbid patient is complex and it is influenced by different factors. The compliance to treatment seems to affect the outcomes of multimorbid patients, but the data in this regard are controversial. The purpose of this research was to investigate the factors that affect compliance in multimorbidity, in order to improve the management of these patients and boost health outcomes. Material and methods. A search strategy was developed, and PubMed database was searched for literature from January 2016 to December 2020, as well as search of reference lists for systemic reviews and meta-analyses and Cochrane guidelines. Information about publication date, subject category, author, country origin, title, abstract, and keywords were extracted, and the full texts were obtained for co-citation analysis. In total, 74 relevant studies and articles were used. Results. Compliance is a multidimensional phenomenon, and it refers to the extent to which a patient’s behavior aligns with agreed recommendations from healthcare providers. Multimorbidity is associated with multiple significant implications: whether physical, psychological, socioeconomic, and treatment challenges that ensue. Non-compliance to prescribed treatment in multimorbid patients is determined by patient’s beliefs about treatment, their knowledge about illness, socioeconomic status, level of treatment burden, and barriers such as costs or inadequate healthcare access. Five sets of compliance determinants are recognized: patient-related (includes beliefs, self-efficacy, and knowledge about illness); socioeconomic status (poor socioeconomic status, unemployment, lack of effective social support, unstable living conditions, and treatment burdens such as medication costs); therapy-related (most notable is complexity of medical regimen, duration of treatment, side effects, and medical support availability to deal with them); health system-related (represent issues due to poor communication); condition-related (represent the illness-related demands faced by the patient including number of conditions, severity of symptoms, level of disability, rate of progression and severity of disease, as well as the availability of effective treatments). Based on revived research, in order to increase the compliance in patients with multimorbidity, were applied different strategies: improvement of the coordination of medical services, promotion of integrated patient-centered care to optimize therapeutic regimens, increase treatment knowledge, and engagement of the patient in treatment decisions. Conclusions. Multimorbidity is associated with poorer medication adherence, and generates multiple challenges related to the complex healthcare needs, multiple consultations, fragmented healthcare services, polypharmacy, increased treatment burden and costs. The relevant factors affecting compliance in multimorbidity were patient-related, socioeconomic-related, therapy-related, health system-related, and condition-related. In order to increase the compliance, we can use patient centered care, empowerment of the patient and better coordination of care.